A paradigm shift towards low-nitrifying systems: The role of biological nitrification inhibition (BNI) - Subbaraoa, Guntur V.; Sahrawat, Kanwar Lal; Nakahara, K.; Rao, Idupulapati M.; Ishitani, Manabu; Hash, C.T.; Kishi, M.; Bonnett, D.; Berry, W.; Lata, Jean-Christophe (Oxford University Press, 2013)
Background: Agriculture is the single largest geo-engineering initiative that humans have initiated on planet Earth, largely through the introduction of unprecedented amounts of reactive nitrogen (N) into ecosystems. A major portion of this reactive N applied as fertilizer leaks into the environment in massive amounts, with cascading negative effects on ecosystem health and function. Natural ecosystems utilize many of the multiple pathways in the N cycle to regulate N flow. In contrast, the massive amounts of N currently applied to agricultural systems cycle primarily through the nitrification pathway, a single inefficient route that channels much of this reactive N into the environment. This is largely due to the rapid nitrifying soil environment of present-day agricultural systems.